Histologic quantification of the seminiferous tubules cells and spermatogenesis yield in Agoutis (Dasyprocta aguti) rised in captivity - Assis-Neto, Antonio Chaves de; Melo, Maria Isabel Vaz de; Carvalho, Maria Acelina Martins de; Miglino, Maria Angélica; Oliveira, Moacir Franco de; Ambrósio, Carlos Eduardo; Silva, Silvana Maria Medeiros de Sousa; Blasquez, Francisco Xavier Hernandez; Papa, Paula de Carvalho; Kfoury Júnior, José Roberto (Brazilian Journal of Veterinary Research and Animal Science, 2003)
This study has as objective to evaluate the spermatogenesis yield of Agoutis rised in captivity, through the rates found between cellular types of the seminiferous epithelium. The results showed that the spermatogenesis yield of the Agoutis since 9 to 14 months of age did not reach the stabilization point. The coefficient of efficiency of the spermatogonium mitoses, did not increase with the age. The meiotic yield, usual spermatogenesis yield and the Sertoli cells index didn't showed numeric variation at function of the age, however, it was not detected by statistic data.